Composição nutricional dos rótulos de “biscoitos tipos integrais” encontrados para comercialização no mercado local - VASCONCELOS, Crystian da Silva (2023)
Whole foods are those that go through a light processing, keeping their fiber and nutrients inside. In this perspective, a nutritional classification is an important means of contact between the product and the consumer, making the preservation of safe and true data. The aim of the study was to evaluate the fiber content and a list of ingredients present on the labels of wholegrain cookies sold in the city of Belém Pa, based on the current legislation on nutritional terms. The data collected were related to the principles of food and nutrition from the point of view of DHAA and SAN. It was found that most brands evaluated use formula as an ingredient in the cereal mix. And when they were related to each other, some biscuit flavors bring disagreement between their fiber types. It can be seen then that the origin of the legislation for these products is extremely important, as it guarantees the consumer's right and favors their freedom to choose good food choices.